The Effects of Fetal Gender on Serum Human Chorionic Gonadotropin and Testosterone in Normotensive and Preeclamptic Pregnancies - Nahid Lorzadeh; Sirous Kazemirad (Journal of Pregnancy)
Introduction. The aim of the present study was to evaluate the effects of fetal sex on serum human chorionic gonadotropin (hCG) and testosterone in normotensive and preeclamptic pregnancies. Materials and Methods. This is a cross-sectional study and 139 women with singleton pregnancies in the third trimester were studied. Seventy-one pregnancies were uncomplicated; among those were 35 male and 36 female fetuses. Sixty-eight pregnancies were complicated by preeclampsia; among those were 35 male and 33 female fetuses. Human chorionic gonadotropin and total testosterone were measured in maternal peripheral blood. Data analyzed by SPSS software. Results. In male-bearing pregnancies, maternal hCG and testosterone serum levels were significantly higher in preeclamptic than normotensive mothers (𝑃<0.001 and 𝑃<0.001, resp.) in female-bearing pregnancies testosterone levels were significantly higher in preeclamptic than normotensive mothers (𝑃<0.001). Total testosterone levels were significantly higher in pregnancies with either gender and significantly higher in mlae-bearing than in female-bearing pregnancies. Conclusion. According to our results, there is a correlation between maternal serum hCG and testosterone levels and preeclampsia. Therefore these tests can be used as routine during 30–38 weeks of gestation. High maternal serum concentrations of these markers can predict preeclampsia.